2009
DOI: 10.1080/13693780802165789
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and some properties of a glycoprotein of 70 kDa (Gp70) from the cell wall ofSporothrix schenckiiinvolved in fungal adherence to dermal extracellular matrix

Abstract: Sporothrix schenckii is the etiological agent of sporotrichosis, a subcutaneous mycosis and an emerging disease in immunocompromised patients. Adherence to target cells is a prerequisite for fungal dissemination and systemic complications. However, information on the cell surface components involved in this interaction is rather scarce. In this investigation, the extraction of isolated cell walls from the yeast phase of S. schenckii with SDS and separation of proteins by SDS-PAGE led to the identification of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Scott and Muchmore (1989) demonstrated that yeast-like cells of S. schenckii contain two proteins of 40 and 70-kDa as the major antigens recognized by sera obtained from sporotrichosis patients; also, it was demonstrated that sera from S. schenckiiinfected mice reacted mainly with a 70-kDa antigen (Nascimento & Almeida 2005). In addition, we have purified and characterized a 70-kDa glycoprotein (Gp70) from the cell wall of S. schenckii yeast-like cells that exhibited adhesion properties (Ruiz-Baca et al 2009). Blotting with a polyclonal anti-Gp70 serum revealed a single spot with a pI of 4.1, which suggested that Gp70 is a S. schenckii-specific protein as it was not immunodetected in other pathogenic and non-pathogenic fungi Here, five antigens of 48, 55, 66, 67 and 70 kDa were immunodetected in the mycelial phase of S. schenckii ATCC 58251, whereas only two antigens of 60 and 70 kDa were identified in yeast cells.…”
Section: Two-dimensional Polyacrylamide Gel Electrophoresis (2d-page)mentioning
confidence: 99%
See 4 more Smart Citations
“…Scott and Muchmore (1989) demonstrated that yeast-like cells of S. schenckii contain two proteins of 40 and 70-kDa as the major antigens recognized by sera obtained from sporotrichosis patients; also, it was demonstrated that sera from S. schenckiiinfected mice reacted mainly with a 70-kDa antigen (Nascimento & Almeida 2005). In addition, we have purified and characterized a 70-kDa glycoprotein (Gp70) from the cell wall of S. schenckii yeast-like cells that exhibited adhesion properties (Ruiz-Baca et al 2009). Blotting with a polyclonal anti-Gp70 serum revealed a single spot with a pI of 4.1, which suggested that Gp70 is a S. schenckii-specific protein as it was not immunodetected in other pathogenic and non-pathogenic fungi Here, five antigens of 48, 55, 66, 67 and 70 kDa were immunodetected in the mycelial phase of S. schenckii ATCC 58251, whereas only two antigens of 60 and 70 kDa were identified in yeast cells.…”
Section: Two-dimensional Polyacrylamide Gel Electrophoresis (2d-page)mentioning
confidence: 99%
“…Glycoprotein staining -Proteins transferred to nitrocellulose membranes after 2D-PAGE were stained with periodic acid-Schiff (PAS) reagent as described previously (Ruiz-Baca et al 2009). …”
Section: Two-dimensional Polyacrylamide Gel Electrophoresis (2d-page)mentioning
confidence: 99%
See 3 more Smart Citations